Women's Role in Smallholder Coffee Management in North Sumatra - Tri Martial; Yusniar Lubis; Ahmad Rizki Harahap; Fahman Urdawi Nasution; Muhammad Arief Tirtana; Mahya Humaira (International Forum of Researchers and Lecturers, 2023)
The main objective of this research is to find out the role of women in the people's coffee management system in North Sumatra. The approach in this research is qualitative. The population of this study comes from 5 city districts in North Sumatra including karo, dairi, humbang hasundutan, simalungun, north tapanuli and mandailing natal districts. The sampling technique uses incidental sampling, namely any female farmer who is found in the field and meets the criteria of the researcher, the sampling number used is 60 farmers. This research data analysis technique uses descriptive analysis. The results of data analysis show that in the management of smallholder coffee plantations in North Sumatra, women take a considerable share. Where 8 out of 10 jobs in coffee management are done by women, while 2 more things are done by men. The roles played by women in coffee management are Land Preparation, Seed Planting, Plant Maintenance, Fruit Picking, Fruit Processing, Seed Drying, Seed Cleaning, Storage, and Distribution, while Pest and Disease Control and seed Grinding are carried out by men.